The influence of heavy doping of TiCoSb intermetallic semiconductor with Cr atoms on structural, kinetic and energetic properties - Stadnyk, Yu.; Romaka, L.; Romaka, V.A.; Horyn, A.; Romaka, V.V.; Lukovskyy, T.; Poplavskyi, O. (Physics and Chemistry of Solid State, 2024)
The structural, electrokinetic, and energetic properties of the TiСо1-xCrxSb semiconductor obtained by doping TiCoSb with Cr atoms introduced into the structure by substituting Co atoms in the crystallographic position 4c were studied. It was shown that in TiСо1-xCrxSb the structural defects of donor and acceptor nature are generated simultaneously in different ratios depending on the impurity concentration. At concentrations of х ≥ 0.02, the conductivity of TiСо1-xCrxSb has a metallic character, and the contribution of current carrier scattering mechanisms to the value of electrical resistivity is of the same order as changes in the concentration of current carriers. It was established that at all temperatures in the range of concentrations x = 0–0.02, the rate of generation of donors exceeds the rate of generation of acceptors, and at concentrations x > 0.02, on the contrary, the rate of generation of acceptors is greater than that of donors. This is indicated by the positive values of thermopower coefficient α(х,Т) of TiСо1-xCrxSb for х > 0.03.